2016
DOI: 10.1136/emermed-2015-205444
|View full text |Cite
|
Sign up to set email alerts
|

Soluble urokinase plasminogen activator receptor (suPAR) in acute care: a strong marker of disease presence and severity, readmission and mortality. A retrospective cohort study

Abstract: ObjectiveSoluble urokinase plasminogen activator receptor (suPAR) is an inflammatory biomarker associated with presence and progression of disease and with increased risk of mortality. We aimed to evaluate the unspecific biomarker suPAR as a prognostic marker in patients admitted to acute care.MethodsThis registry-based retrospective cohort study included 4343 consecutively admitted patients from the Acute Medical Unit at a large Danish university hospital. Time to readmission and death were analysed by multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
113
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 27 publications
7
113
0
2
Order By: Relevance
“…This applies to acute as well as chronic diseases and infectious as well as noncommunicable diseases, including clinical conditions investigated in children (Schaefer et al, 2017;S ßirino glu et al, 2017;Wittenhagen et al, 2011;Wrotek, Jackowska, & Pawlik, 2015). suPAR appears to reflect the health status or inflammatory burden of an individual, and chronic multimorbid patients have higher suPAR levels than patients with fewer chronic diseases (Rasmussen et al, 2016), while healthy people have low suPAR levels (Haupt et al, 2014). In the general population, suPAR has been found to increase with age and unhealthy lifestyle, with smoking and morbid obesity being major drivers of increased suPAR levels (Haupt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This applies to acute as well as chronic diseases and infectious as well as noncommunicable diseases, including clinical conditions investigated in children (Schaefer et al, 2017;S ßirino glu et al, 2017;Wittenhagen et al, 2011;Wrotek, Jackowska, & Pawlik, 2015). suPAR appears to reflect the health status or inflammatory burden of an individual, and chronic multimorbid patients have higher suPAR levels than patients with fewer chronic diseases (Rasmussen et al, 2016), while healthy people have low suPAR levels (Haupt et al, 2014). In the general population, suPAR has been found to increase with age and unhealthy lifestyle, with smoking and morbid obesity being major drivers of increased suPAR levels (Haupt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting suPAR is a stable circulating molecule with intrinsic chemotactic properties (Resnati et al, 2002), and the level of suPAR is thought to reflect the overall immune activity of an individual (Desmedt et al, 2017). suPAR levels are elevated across a wide range of diseases (Rasmussen et al, 2016), including cardiovascular disease (Persson et al, 2014), type 2 diabetes (Guthoff et al, 2017), cancer (Sorio et al, 2011;Tarpgaard et al, 2015), renal disease (Hayek et al, 2015), and infections (Donadello et al, 2014). In addition, suPAR predicts mortality, both in the general population and in patient populations (Eugen-Olsen et al, 2010;Rasmussen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rasmussen et al 35 found that the total plasma uPAR level in acutely admitted patients was strongly associated with 30-day mortality after admission. Also, the total plasma uPAR level in the general population may be associated with an increased risk of developing cancer, cardiovascular disease and type 2 diabetes later on in life,36 which links plasma uPAR levels to the Charlson comorbidity scores demonstrated in the present study as well as in previous studies 5.…”
Section: Discussionmentioning
confidence: 99%
“…However, since stroke was included as a composite endpoint in the present study, we were unable to test whether suPAR only explained the difference in the risk of ischaemic and not haemorrhagic stroke or whether suPAR also predicts haemorrhagic stroke independently of blood pressure. Association between suPAR and IHD risk has been shown earlier in a large population cohort (36) , and since suPAR is highly predictive of mortality (3)(4)(5)(6)(7) , we speculate that the association between suPAR and IHD risk may be driven by high case fatality rates in historic cohorts (37)(38)(39) . Missing values regarding survival analyses generally seem to produce a slight underestimation of effect of diet on IHD risk and a slight overestimation of the effect of diet on stroke risk.…”
Section: Discussionmentioning
confidence: 51%